Benefits of a pharmacology antimalarial reference standard and proficiency testing program provided by the Worldwide Antimalarial Resistance Network (WWARN). - Lourens, C; Lindegardh, N; Barnes, K; Guerin, P; Sibley, C; White, N; Tarning, J (American Society for Microbiology, 2014)
Comprehensive assessment of antimalarial drug resistance should include measurements of antimalarial blood or plasma concentrations in clinical trials and in individual assessments of treatment failure so that true resistance can be differentiated from inadequate drug exposure. Pharmacometric modeling is necessary to assess pharmacokinetic-pharmacodynamic relationships in different populations to optimize dosing. To accomplish both effectively and to allow comparison of data from different laboratories, it is essential that drug concentration measurement is accurate. Proficiency testing (PT) of laboratory procedures is necessary for verification of assay results. Within the Worldwide Antimalarial Resistance Network (WWARN), the goal of the quality assurance/quality control (QA/QC) program is to facilitate and sustain high-quality antimalarial assays. The QA/QC program consists of an international PT program for pharmacology laboratories and a reference material (RM) program for the provision of antimalarial drug standards, metabolites, and internal standards for laboratory use. The RM program currently distributes accurately weighed quantities of antimalarial drug standards, metabolites, and internal standards to 44 pharmacology, in vitro, and drug quality testing laboratories. The pharmacology PT program has sent samples to eight laboratories in four rounds of testing. WWARN technical experts have provided advice for correcting identified problems to improve performance of subsequent analysis and ultimately improved the quality of data. Many participants have demonstrated substantial improvements over subsequent rounds of PT. The WWARN QA/QC program has improved the quality and value of antimalarial drug measurement in laboratories globally. It is a model that has potential to be applied to strengthening laboratories more widely and improving the therapeutics of other infectious diseases.